Choice Model of The Modes of Marine Transportation with Regretion Logistic Method (Case Study in North Island, Maluku) - Buamona, Fachmi; Widodo, Agus; Purwanto, Imam Nurhadi (Fakultas Teknik UMMU, 2019)
Transportation method was first proposed by FL.Hitchcock in 1941. Presented in a study of The Distribustion of a Product From Several Sources to Numerous Localities. The use of maximum likelihood method (MLE) is to estimate the parameters of binomial logistic regression model, which has been investigated by Aragon et al (1992), Cabrera et al (2005) also Grigolon et al (2014). Linear regression model used in this study is a binomial logistic regression model. The aim of this study; Getting estimates or predictor factors mempengaruhui election marine transportation modes and models of sea transport modal choice as well as getting the SWOT analysis of the factors marine transport modal choice ferry and speedboat in North Maluku. From the results of data analysis statistical tests that have significant levels of very influential is the travel time Generated bivariate binary logistic regression model for marine transport modes ferry and speedboat. Marine transportation mode indicator strategy ferries total internal strengths and weaknesses of (-0.48) and total indicator of external opportunities and threats strategy of (0.49). Indikato modes of transport speedboats total-internal strategy indicator of the strengths and weaknesses (-0.40) and total indicators of external opportunities and threats strategy of (0.36).